Does surface anodisation of titanium implants change osseointegration and make their extraction from bone any easier? - Langhoff, J. D.; Mayer, J.; Faber, L.; Kaestner, S. B.; Guibert, G.; Zlinszky, K.; Auer, J. A.; Rechenberg, B. von (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
Objectives: Titanium implants have a tendency for high bone-implant bonding, and, in comparison to stainless steel implants are more difficult to remove. The current study was carried out to evaluate, i) the release strength of three selected anodized titanium surfaces with increased nanohardness and low roughness, and ii) bone-implant bonding in vivo. These modified surfaces were intended to give improved anchorage while facilitating easier removal of temporary implants. Material and methods: The new surfaces were referenced to a stainless steel implant and a standard titanium implant surface (TiMAX™). In a sheep limb model, healing period was 3 months. Bone-implant bonding was evaluated either biomechanically or histologically. Results: The new surface anodized screws demonstrated similar or slightly higher bone-implantcontact (BIC) and torque release forces than the titanium reference. The BIC of the stainless steel implants was significant lower than two of the anodized surfaces (p=0.04), but differences between stainless steel and all titanium implants in torque release forces were not significant (p=0.06). Conclusion: The new anodized titanium surfaces showed good bone-implant bonding despite a smooth surface and increased nanohardness. However, they failed to facilitate implant removal at 3 months.
Keywords: Titanium; anodised implants; removal torque; bone-implant bonding; sheep